Feasibility Analysis of the Neng Geulis Kebaya Rental Business: Opportunities and Challenges in the Local Fashion Industry - Karim, Fakia Zikri Abdul; Zain, Hanifah; Adinda, Najua Mayang; Hidayah, Nurul; Rifki, Muhamad Abdul; Asyfa, Putri Dela (Lentera Ilmu Nusantara, 2025)
The ever-growing kebaya trend, coupled with the increasingly elegant and diverse use of modern kebayas, has led to an increase in demand for kebayas. The kebaya rental business has emerged as a promising opportunity, as the high price of kebayas has led many consumers to choose to rent rather than buy, especially those who only need kebayas for specific occasions. This study aims to assess the feasibility of the local fashion business Kebaya Neng Geulis from various aspects, namely marketing, human resources, operations, and finance, with the objective of providing a structured evaluation that contributes to the literature on small-scale fashion business feasibility. This study uses a descriptive approach to understand the opportunities and challenges that this kebaya rental business may face, where data were analyzed to highlight both financial and non-financial aspects systematically. The kebaya rental system is an economical solution for consumers, as it provides access to a variety of quality kebaya models at a more affordable price. The findings of this study indicate that the Kebaya Neng Geulis business meets the feasibility criteria from various aspects reviewed and is feasible to run, offering a novel contribution by emphasizing the business model’s adaptability in addressing consumer preferences while providing implications for entrepreneurs seeking to innovate within the traditional fashion sector.